Cutaneous lipogenesis: precursors utilized by guinea pig skin for lipid synthesis - VICTOR R. WHEATLEY (Journal of Lipid Research, 1971)
Cutaneous lipogenesis was studied, using a guinea pig ear slice incubation technique, for the following precursors: acetate, propionate, butyrate, glucose, pyruvate, lactate, succinate, citrate, and selected amino acids. Active lipogenesis was observed with short-chain fatty acids, glucose, pyruvate, lactate, and with the amino acids, alanine, leucine, and isoleucine. Glucose was shown to play an important role in cutaneous lipogenesis; it is a major precursor of lipid and the only compound able to stimulate lipogenesis. Its incorporation into lipid is unaffected by either insulin or epinephrine. The incorporation rates of glucose-1- and glucose-6-14C were equal, suggesting the possibility that generation of NADPH by the pentose-phosphate pathway is minimal. Citrate, succinate, and pyruvate all failed to stimulate the incorporation of acetate ; on the other hand, citrate, isocitrate, malate, malonate, and ATP caused inhibition of the incorporation of glucose. Significant incorporation of tritium from tritiated water was observed, and the order of magnitude suggests that it can be used as an independent assessment of the rate of cutaneous lipogenesis. Bicarbonate was not only able to stimulate the rate of incorporation of a variety of precursors but was also incorporated into fatty acids to a measurable extent. The mode of incorporation of propionate was unusual, since propionate-1-14C was incorporated into fatty acids at more than double the rate for propionate-2-14C, suggesting incorporation of the carboxyl carbon without the rest of the molecule. Mechanisms are suggested to account for the carbon dioxide fixation, but we are unable to completely explain the anomalous results for propionate.